O plano de recuperação judicial como negócio jurídico plurilateral: a análise da existência, da validade e da eficácia - Melo, Cinira Gomes Lima (2016)
The company's crisis is a growing phenomenon and its economic and social impacts reflect on all those involved in economic activity: other business owners, workers, consumers, State, among others. The Law n. 11.101/2005 regulates the Judicial and Extrajudicial Recovery of business in crisis, establishing procedures that can be adopted to attempt to maintain the production activity and employment of workers in case of installed crisis. It is important before such a scenario, to study the legal treatment of the company's crisis, to ensure the necessary legal certainty to those who exercise economic activity. Therefore relevant to study the judicial recovery plan, as an essential element to define the concrete parameters of passive satisfaction and reset goals and purposes of business activity, to establish their legal status and also limit the elements of existence, their validity requirements and the effectiveness factors